DEVELOPMENT OF TECHNOLOGY OF FLOUR CONFECTIONERY PRODUCTS WITH APPLICATION OF PRODUCTS OF PROCESSING OF BERRIES - M. S. Voronina; N. V. Makarova (Современная наука и инновации, 2022)
Lour confectionery products are in great demand and popularity among the population. The main drawback of products is that their excessive consumption upsets the balance of diets for food substances and energy value, which is explained by the high content of fat, carbohydrates and low enough, and in some cases the complete absence of dietary fibers, minerals and vitamins.